Functionalized natural cellulose fibres for the recovery of uranium from seawater - Tellería Narvaez, Adrian (2020)
Sisal fibres have been functionalized with aminotrismethylenephosphonic acid (ATMP) and N-(phosphonomethyl)glycine (glyphosate) by hydrothermal reaction in dilute solutions of the phosphonates at temperatures in the range 120-180 °C. The hydrothermal treatment results in delignification and anchoring of the phosphonate. The functionalized fibers show greatly enhanced efficiency for the recovery of uranium from seawater relative to the untreated fibres and possess capacities up to 16 mg g-1 in spiked seawater and relatively rapid kinetics reaching a maximum uptake in under 1 h.